Analisis Penafsiran Hakim terhadap Nusyuz dan Hak Nafkah 'Iddah dalam Pasal 152 KHI - Afadhoh, Chrisna Lailatul; Bahri, Syaiful; Fakhria, Sheila (RechtJiva, 2026)
Differences in the interpretation of the concept of nusyuz under Article 152 of the Compilation of Islamic Law (Kompilasi Hukum Islam—KHI) have led to differing applications of the law concerning a former wife's entitlement to iddah maintenance following divorce. One such difference is reflected in Decision Number 277/Pdt.G/2020/PA.Kdr., in which the panel of judges awarded iddah maintenance and mut'ah to a wife who had been declared nusyuz. This study aims to analyze the judges' method of interpreting the concept of nusyuz in the decision and to assess its conformity with the concept of nusyuz according to the Shafi'i school of Islamic jurisprudence. This research employs a normative legal method using an Islamic law (fiqh) approach. The primary legal materials consist of the Compilation of Islamic Law, relevant statutory regulations, and Decision Number 277/Pdt.G/2020/PA.Kdr., while the secondary legal materials include classical and contemporary fiqh literature, books, and scholarly journal articles. Legal materials were collected through library research and document analysis and were subsequently examined using a prescriptive legal approach. The findings indicate that the panel of judges applied a systematic interpretation by construing Article 152 in conjunction with Article 151 of the KHI, thereby interpreting nusyuz as a violation of a former wife's obligations during the iddah period. Based on this interpretation, nusyuz committed during the marriage does not extinguish the former wife's entitlement to iddah maintenance and mut'ah. From the perspective of the Shafi'i school of Islamic jurisprudence, however, this interpretation is not entirely consistent with the classical concept of nusyuz, which defines it as a wife's disobedience to her marital obligations while the marriage remains legally valid. Nevertheless, the judges' interpretation reflects an approach oriented toward protecting women's economic rights after divorce through considerations of justice and public benefit (maslahah).